PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN PENGAWASAN TERHADAP KOMITMEN KARYAWAN PT. TELKOMSEL PEKANBARU - Sari, Tia Angelia; Rifqi, Ahmad; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Human Resources is very important in an organization, because the effectiveness and success of an organization depends on the quality and performance of existing human resources in the organization. Performance of human resources (members) which will encourage the emergence of employee commitment. Some aspects required and also can determine the level of employee commitment levels PT. Telkomsel Pekanbaru is Organizational Culture, Leadership Style. This study aimed to analyze the influence of Organizational Culture, Leadership Styleof Employee Commitment PT. Telkomsel Pekanbaru. This study uses multiple linear regression analysis using SPSS. The population used is the number of employees of PT. Telkomsel with 134 people. The amount of sample used as many as 100 people. The results showed that there is a positive and significant impact between Organizational Culture, Leadership Styleof Employee Commitment Value coefficient of determination (Adjusted R Square) is equal to 0.546%, or 54.6% mean variation influenced variable changes Employee Commitment Organizational Culture, Leadership Style and Supervision by 54.6% and the remaining 45.4% is influenced by other factors.Keywords : Organizational Culture, Stylesof Leadership, and Employee Commitmen